Protective Effect of Lycopene on Ifosfamide-Induced Mitophagy through Pink, Parkin, and LC3-I/II Pathway in Testicular Tissue - Ali Thoulfikar A. Imeer; Moona Roshanfekr Rad; Sara Abedi (International Journal of Fertility and Sterility)
Background: Ifosfamide (IFO) is a widely used chemotherapeutic agent that exerts cytotoxic effects through various mechanisms, including the induction of apoptosis and oxidative stress. However, its use is associated with detrimental effects on male reproductive health, including mitochondrial dysfunction and oxidative stress-induced damage. Mitophagy, a selective autophagic process, plays a crucial role in maintaining mitochondrial homeostasis during spermatogenesis. This study aimed to investigate the potential protective effect of lycopene against IFO-induced mitophagy in testicular tissue. We evaluated the expression levels of key mitophagy regulators Pink1, Parkin, and LC3-I/ II in testicular tissue of rats treated with IFO alone or in combination with lycopene.Materials and Methods: In this experimental study, 24 mature male Wistar rats (250 g ± 25) were divided into control (received normal saline), IFO-sole (received 250 mg/kg, single dose, ip), lycopene (25 mg/kg, orally), and IFO+lycopene groups. Following 60 days, the rats were euthanized and the testicles were dissected out. The expression levels of Pink1, Parkin, and LC3-I/II were evaluated using qRT-PCR and immunohistochemistry (IHC) techniques.Results: Our findings demonstrated that IFO significantly upregulated Pink1, Parkin, and LC3-I/II expression at both mRNA and protein levels compared to controls. Conversely, lycopene administration mitigated these increases induced by IFO, suggesting its potential to attenuate IFO-induced mitophagy. Immunohistochemistry analysis confirmed the protective effect of lycopene, showing reduced expression levels of Pink1, Parkin, and LC3-I/II in the presence of lycopene following IFO treatment.Conclusion: These results underscore lycopene's role as a potent protective agent that can mitigate IFO-induced mitophagy in testicular tissue. Further research into the underlying mechanisms of lycopene's protective effects will be crucial for developing therapeutic strategies to preserve male fertility during IFO treatment.